Peningkatan Produktivitas Insan Pendidikan Ditengah Pandemi Covid-19 - Ramdan, Galih Muhammad; Putri, Anisa Devisa; Sholahudin, Hary; Munajat, Ikbal; Apriliani, Insani; Jaya, Mochamad; Azmi, Muhammad; Alhakeem, Reinalgy Azni; Zulfiansyah, Rezky; Asgara, Zidan; Nashrulloh, Muhammad Rikza (Institut Teknologi Garut, 2022)
Responding to the spread of the COVID-19 pandemic, the Indonesian government implemented a series of policies, one of which is distance learning. This approach is expected to be able to minimize social interaction and reduce the number of positive cases of COVID-19. Although in its implementation distance learning is considered not optimal. Along with the development of information and communication technology. People find alternative social interactions through virtual communities. In an effort to optimize the potential of distance learning. Devotion is done to the virtual community who are people of education. The method used is in the form of input, problem solving and output stages through a series of webinars and dissemination of educational content through social media. Aiming to increase the productivity of education personnel during the COVID-19 pandemic. The conclusion results state that there has been an increase in capacity related to productivity in education personnel from what was very poor to very good.